2009
DOI: 10.3899/jrheum.080574
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the 1997 Updated Classification Criteria for Systemic Lupus Erythematosus: Epidemiology, Disease Presentation, and Patient Management

Abstract: ABSTRACT. Objective. The 1997 update of the American College of Rheumatology classification criteria (ACR97) for systemic lupus erythematosus (SLE) has not been validated. We determined to what extent their introduction influenced the epidemiology and clinical characteristics of the disease in northern Norway. Methods. Annual incidence and point-prevalence rates, clinical manifestations, and outcome were determined in an inception cohort of patients with SLE in northern Norway, included between 1996 and 2006, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 39 publications
4
26
0
Order By: Relevance
“…Previous studies have found a prevalence of lupus nephritis between 20% and 30%. 10,41 In recent years, however, a decrease has been observed, 42 and this finding is in agreement with the findings in our study. Misclassification of cases might explain the relatively few cases of lupus nephritis in our study.…”
Section: Discussionsupporting
confidence: 96%
“…Previous studies have found a prevalence of lupus nephritis between 20% and 30%. 10,41 In recent years, however, a decrease has been observed, 42 and this finding is in agreement with the findings in our study. Misclassification of cases might explain the relatively few cases of lupus nephritis in our study.…”
Section: Discussionsupporting
confidence: 96%
“…Antiphospholipid Ab have become part of the classification process for SLE, 13 and the overall prevalence of aPL (48%) agrees with other series. 30,31 While inclusion of aPL as a classification criterion has not led to large changes in the clinical spectrum of SLE at diagnosis, 12 they are likely connected to the remarkably high (7.5%) overall frequency of ischaemic events in this cohort with a mean age of 35 years. The frequencies for vascular events in the first years of disease (cerebrovascular events 4%, venous thrombosis 2% and angina pectoris 1%) confirm the need for better markers to identify patients at vascular risk, as current aPL assays are not specific enough.…”
Section: Discussionmentioning
confidence: 99%
“…6,[40][41][42] This will likely require use of immunosuppressive therapy for some time to come, even though the potential benefits of such treatment are offset by increased infectious complications. 8 Thus, in addition to increased efforts for early diagnosis at a less severe disease stage, 12 there is a clear need for less toxic but efficient ways of reducing early disease activity, such as through B-cell depletion or inactivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[28][29][30] For the current study, clinical and routine laboratory data as well as blood samples for storage were collected simultaneously during an extended outpatient visit. Thrombocytopenia was defined as platelet counts <150 and was considered mild with platelet counts between 100-150, moderate between 100-50 and severe <50.…”
Section: Patientsmentioning
confidence: 99%